2020
DOI: 10.1523/eneuro.0300-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Auditory and Binaural Spatial Hearing in a Fragile X Syndrome Mouse Model

Abstract: The auditory brainstem compares sound-evoked excitation and inhibition from both ears to compute sound source location and determine spatial acuity. Although alterations to the anatomy and physiology of the auditory brainstem have been demonstrated in fragile X syndrome (FXS), it is not known whether these changes cause spatial acuity deficits in FXS. To test the hypothesis that FXS-related alterations to brainstem circuits impair spatial hearing abilities, a reflexive prepulse inhibition (PPI) task, with vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 63 publications
6
23
4
Order By: Relevance
“…130,[134][135][136][137][138][139][140][141][142][143][144][145] Other studies reported unaltered, enhanced ASR, or reduced PPI. 134,138,139,142 Potential contributors to these discrepancies include, but are not limited to, the genetic background, 140,146 sex (147; but also see137), age, 145 and the sound level for triggering ASR. 140 Particularly, strainspecific differences have been reported in a variety of behavioral phenotypes following Fmr1 deletion 142 and it is known that different mouse strains exhibit varying degrees of ASR in wild-type mouse strains.…”
Section: Altered Asr and Ppimentioning
confidence: 99%
See 2 more Smart Citations
“…130,[134][135][136][137][138][139][140][141][142][143][144][145] Other studies reported unaltered, enhanced ASR, or reduced PPI. 134,138,139,142 Potential contributors to these discrepancies include, but are not limited to, the genetic background, 140,146 sex (147; but also see137), age, 145 and the sound level for triggering ASR. 140 Particularly, strainspecific differences have been reported in a variety of behavioral phenotypes following Fmr1 deletion 142 and it is known that different mouse strains exhibit varying degrees of ASR in wild-type mouse strains.…”
Section: Altered Asr and Ppimentioning
confidence: 99%
“…Interestingly, studies of Fmr1 knockout mice show mixed results, perhaps because of the very different hearing range of humans and mice. Many studies found reduced ASR to startle sounds at the level of 90‐120 dB, along with enhanced PPI, as compared to age‐matched wild‐type mice . Other studies reported unaltered, enhanced ASR, or reduced PPI .…”
Section: Audition‐associated Behavioral Changes In Fxsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, research has shown FMRP expression in mature oligodendrocytes (OLs), potentially explaining how loss of FMRP impacts myelination (Wang et al, 2004;Giampetruzzi et al, 2013). The mechanisms by which binaural hearing is impaired in people with FXS and ASD are unknown, however there is evidence the auditory brainstem is involved (Kulesza and Mangunay, 2008;Kulesza Jr. et al, 2011;Wang et al, 2014;Rotschafer et al, 2015;Garcia-Pino et al, 2017;McCullagh et al, 2017McCullagh et al, , 2020aZorio et al, 2017;Curry et al, 2018;El-Hassar et al, 2019;Lu, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Any alteration in this pathway that changes the precision and timing of this circuit will lead to substantial difficulties in the ability to separate competing auditory streams and localize sound, as occurs in ASD. Interestingly, increased changes to latency for both behavioral and physiological measures seem to be one of the more repeatable phenotypes in FXS mice (Kim et al, 2013a;McCullagh et al, 2020a, but see Rotschafer et al, 2015El-Hassar et al, 2019). One way in which changes to myelination in the auditory brainstem would likely manifest is through changes in the speed of synaptic transmission, and therefore latency of auditory brainstem timing.…”
Section: Introductionmentioning
confidence: 99%